Fish type I and type II interferons: composition, receptor usage, production and function. (2nd May 2019) - Gan, Zhen; Chen, Shan Nan; Huang, Bei; Zou, Jun; Nie, Pin
Abstract: Interferons (IFNs) have been reported in vertebrates from fish to mammals. To date, two types of IFNs, i.e. type I and type II IFNs have been reported in a range of fish species in aquaculture. In fish, type I IFNs are clarified into group I and group II, with two cysteines and four cysteines, and further into subgroups a, d, e, h, and b, c, f, respectively. Group I IFNs appear to exist in all fish species, whereas group II IFNs are discovered only in certain species such as cyprinids, salmonids and perciform fish. It seems preferentially functional that group I IFNs signal through cytokine receptor family B (CRFB) 5 and CRFB1, while group II IFNs through CRFB5 and CRFB2. But they all initiate a same signalling pathway for the expression of interferon induced genes. The information about the production and the function of type I IFNs in fish are further summarized in the review. Interestingly, two members of type II IFNs, IFN‐γ and a unique member, IFN‐γ related gene (IFN‐γrel) exist in fish, and IFN‐γ and IFN‐γrel can separately become homodimers for signalling through CRFB13, CRFB17, CRFB6 and CRFB17, respectively. In addition, the variation in the composition of type I and type II IFNs as well as in their receptors in some cyprinid and salmonid fish has also been reviewed. It is suggested that future perspectives for the research on type I and type II IFNs in fish are outlined from a comparative and evolutionary point of view.